Political, social, and human capital in the face of climate change: Case of rural Indonesia. Issue 5 (19th October 2020) - Utami, Arini Wahyu; Cramer, Lori A.
ABSTRACT: This study examines the link between political capital and climate change adaptation, and tests the relationship among political capital, social capital, and human capital. Political capital is studied through power distribution, voice, and connection in three rural villages in Java, Indonesia. This study finds that rural communities with a more distributed power structure are more likely to take the initiative to mobilize efforts by using their own resources to cope and adapt to climate change. Analysis with binary-logistic regression shows that social capital is a better predictor in the exercise of political capital than human capital. While the act of giving gifts to neighbors is associated with more community activism, receiving gifts from neighbors and membership in community groups tend to lower the activism.